Examining a Successful Industrial Training Program Model: Inter-relationship Among the Three Main Stakeholders: Students, University and Host Companies - Fong Woon, Lai (2007)
The aim of this study is to examine the success of the industrial training program for undergraduates from the engineering and technology disciplines in Universiti Teknologi PETRONAS (UTP). The analysis revolves around the perspectives of three main stakeholders, namely the students undergoing the program, the university organizing the program and the training providers participating in the program (host companies). The study investigates whether the following objectives of UTP’s industrial training program have been met: i) to integrate theory with practice ii) to introduce students to work culture and industrial practices iii) to expose students to the industry and potential employers The study also investigates the extent of the host companies being a critical success factor in determining the effective implementation of the university’s industrial internship program. The relevant data for this study was collected via questionnaires from university students and supervisors from host companies. Statistical procedures are used to analyze the data. It is envisaged that this study will provide useful information for the three stakeholders to re-examine and enhance the efficacy of the industrial training program.